Legal Guarantees Against Breach of International Trade Contracts Due to Non-Conformity of Goods Details reviewed from the CISG - Fita dwi pratiwi (Jurnal Justiciabelen, 2022)
in international contract transactions are currently not a difficult thing, the existence of these various technological advances provides a considerable opportunity and opportunity for the international community to establish cooperative relations between them. The execution of the contract in various ways can certainly cause problems or obstacles, especially in long-term contracts, it can be due to discrepancies in the details of the goods sold, the existence of force majeure circumstances that can result in the contract being unenforceable, or there may be changes in circumstances, such as political crises, currency fluctuations, economic crises. However, this study will focus more on discussing legal guarantees against violations of international trade contracts due to discrepancies in the details of goods reviewed from the CISG. International business cooperation transactions are the study of private law, where in private law, the law provides wider opportunities for each party to make, promise and implement the clauses they make. However, it is undeniable that to be able to carry out these activities, the parties must carefully understand and understand the legal rules that exist in the State of each party. The research method carried out uses normative juridical, i.e legal studies carried out by using examining library materials or secondary legal materials. Meanwhile, in collecting data, it is carried out with two approaches, namely the conceptual method and the statutory technique. The purpose of this research is to find out how the legal guarantees that apply in international trade contract law if there is a violation in the contract due to discrepancies in the details of the goods received and what form of settlement efforts can be made by sellers and buyers in international trade contracts. This research resulted in a relationship to the legal guarantee of a breach of an international trade contract and what efforts were made by the parties to the matter in terms of the CISG international contract transactions are currently not a difficult thing, the existence of these various technological advances provides a considerable opportunity and opportunity for the international community to establish cooperative relations between them. The execution of the contract in various ways can certainly cause problems or obstacles, especially in long-term contracts, it can be due to discrepancies in the details of the goods sold, the existence of force majeure circumstances that can result in the contract being unenforceable, or there may be changes in circumstances, such as political crises, currency fluctuations, economic crises. However, this study will focus more on discussing legal guarantees against violations of international trade contracts due to discrepancies in the details of goods reviewed from the CISG. International business cooperation transactions are the study of private law, where in private law, the law provides wider opportunities for each party to make, promise and implement the clauses they make. However, it is undeniable that to be able to carry out these activities, the parties must carefully understand and understand the legal rules that exist in the State of each party. The research method carried out uses normative juridical, i.e legal studies carried out by using examining library materials or secondary legal materials. Meanwhile, in collecting data, it is carried out with two approaches, namely the conceptual method and the statutory technique. The purpose of this research is to find out how the legal guarantees that apply in international trade contract law if there is a violation in the contract due to discrepancies in the details of the goods received and what form of settlement efforts can be made by sellers and buyers in international trade contracts. This research resulted in a relationship to the legal guarantee of a breach of an international trade contract and what efforts were made by the parties to the matter in terms of the CISG